SARS-CoV-2 Evolution and Patient Immunological History Shape the Breadth and Potency of Antibody-Mediated Immunity - Manali, Maria; Bissett, Laura A; Amat, Julien A R; Logan, Nicola; Scott, Sam; Hughes, Ellen C; Harvey, William T; Orton, Richard; Thomson, Emma C; Gunson, Rory N; Viana, Mafalda; Willett, Brian; et al. (The Journal of infectious diseases, 2022)
Abstract Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), humans have been exposed to distinct SARS-CoV-2 antigens, either by infection with different variants, and/or vaccination. Population immunity is thus highly heterogeneous, but the impact of such heterogeneity on the effectiveness and breadth of the antibody-mediated response is unclear. We measured antibody-mediated neutralization responses against SARS-CoV-2Wuhan, SARS-CoV-2α, SARS-CoV-2δ, and SARS-CoV-2ο pseudoviruses using sera from patients with distinct immunological histories, including naive, vaccinated, infected with SARS-CoV-2Wuhan, SARS-CoV-2α, or SARS-CoV-2δ, and vaccinated/infected individuals. We show that the breadth and potency of the antibody-mediated response is influenced by the number, the variant, and the nature (infection or vaccination) of exposures, and that individuals with mixed immunity acquired by vaccination and natural exposure exhibit the broadest and most potent responses. Our results suggest that the interplay between host immunity and SARS-CoV-2 evolution will shape the antigenicity and subsequent transmission dynamics of SARS-CoV-2, with important implications for future vaccine design. The breadth and potency of the antibody-mediated response against SARS-CoV-2 is influenced by the exposure type, the number of exposures, and the genotype of the infecting variant. Patients with mixed immunity acquired by vaccination and infection exhibit most effective responses. Lay Summary Neutralizing antibodies provide protection against viruses and are generated because of vaccination or prior infections. The main target of anti-SARS-CoV-2 neutralizing antibodies is a protein called spike, which decorates the viral particle and mediates viral entry into cells. As SARS-CoV-2 evolves, mutations accumulate in the spike protein, allowing the virus to escape antibody-mediated immunity and decreasing vaccine effectiveness. Multiple SARS-CoV-2 variants have appeared since the start of the COVID-19 pandemic, causing various waves of infection through the population and infecting—in some cases—people that had been previously infected or vaccinated. Because the antibody response is highly specific, individuals infected with different variants are likely to have different repertoires of neutralizing antibodies. We studied the breadth and potency of the antibody-mediated response against different SARS-CoV-2 variants using sera from vaccinated people as well as from people infected with different variants. We show that potency of the antibody response against different SARS-CoV-2 variants depends on the particular variant that infected each person, the exposure type (infection or vaccination) and the number and order of exposures. Our study provides insight into the interplay between virus evolution and immunity, as well as important information for the development of better vaccination strategies.